Spin labeled nucleic acids. - Caspary, W J (1976)
Homopolyribonucleotides and E. coli DNA wer spin labeled with an iodoacetamide-nitroxide compound. The extent of labeling is highly dependent upon the nature of the base and the secondary structure of the nucleic acid. This spin label-polymer linkage is unstable at high temperatures and in phosphate buffers. In order to determine the effect of changes in the environment of nucleic acids on the esr signals of their attached spin labels, the polynucleotides were subjected to temperature and viscosity perturbations. An increase in temperature (T) affects a linear decrease in the anisotropy factor of the esr signal. The log tau (tau = correlation time) versus (1/T) profile is linear with a positive slope when the spin label is attached to single stranded polynucleotides but exhibits discontinuities at certain critical temperatures when attached to the duplexes poly (As-U) and poly (I-Cs). These critical temperatures are lower than the optical Tm. Logarithmic increase in viscosity was found to produce a linear increase in tau in aqueous sucrose solutions.